Teores de oleuropeína e compostos fenólicos em extratos foliares de cultivares de oliveira no sul do Brasil - Santos, Jullie dos (2022)
Olive leaf extract (Olea europaea L.) is well known for the bioactivity of its phytoconstituents (oleuropein, hydroxytyrosol, flavonoids and derivatives) with antioxidant activity. The objective of this study was to determine the yield of leaf extracts from olive trees cultivated in Rio Grande do Sul, as well as to identify and quantify the levels of oleuropein and simple phenolic compounds and flavonoids present in the extracts. Thus, for experiment 1, four collections of leaves of olive tree cv. Arbequina, one collection per season, during a period of one year, in the municipality of Formigueiro, RS. For experiment 2, in addition to cv. Arbequina, leaves were also collected from cvs. Koroneiki and Manzanilla, in the municipality of São Sepé, RS. The extractions were performed in a Soxhlet apparatus, with ethanol. Chemical analysis of the samples was performed using a UHPLC (Ultra-HighPerformance Liquid Chromatography) device coupled to a DAD detector (Diode Array Detector) for quantitative determination of oleuropein, flavonoids and simple phenolic compounds. The first experiment was carried out in a completely randomized design, consisting of four treatments corresponding to the four seasons of the year, with three replications per treatment. As a result of experiment 1, the autumn season was identified as the most favorable to obtain the highest extract yield, while spring provided the highest content of the constituent oleuropein, compared to the other seasons. The second experiment was carried out in a 3x4 bifactorial scheme (three olive cultivars x four seasons), comprising 12 treatments, with three replications each. The results of the second experiment indicate the cv. Manzanilla and the autumn season as the best combination to obtain the highest extract yield. The chemical analysis of the samples allowed the identification of the constituents oleuropein, hydroxytyrosol, rutin, quercetin and caffeic acid in different concentrations. The results suggest that cv. Manzanilla is the most suitable for obtaining high concentrations of oleuropein during autumn and caffeic acid during summer. The cv. Koroneiki showed the highest levels of hydroxytyrosol in winter and cv. Arbequina proved to be the most suitable for obtaining the constituents rutin and quercetin, both in summer. These results can contribute in a relevant way to Brazilian olive growing, bringing information of interest to different sectors.